Self-Efficacy and Adherence as Predictors of Quality of Life in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study at Jemursari Islamic Hospital, Surabaya - ilmi nafiah; Difran Nobel Bistara; Chilyatiz Zahroh; Riska Rohmawati; Susanti; Priyagung Gusmantara (Universitas Nahdlatul Ulama Surabaya, 2026)
Type 2 diabetes is associated with a progressive decline in patients' quality of life (QoL). Self-efficacy and adherence are critical behavioral determinants that influence disease management and outcomes. This study examines the correlation between self- efficacy and adherence to quality of life in patients with type 2 diabetes mellitus. This study used a correlational analytic research design with a cross-sectional approach. The study was conducted at Islamic Hospital Jemursari, Surabaya, from August to October 2024. The population consisted of 307 patients with diabetes, and 174 respondents were selected through purposive sampling. Data were collected using validated questionnaires: the Diabetes Management Self-Efficacy Scale (DMSES), the Adherence to Diabetes Questionnaire (ADQ), and the Diabetes Quality of Life (DQOL)questionnaire. Data analysis was the Spearman's Rank correlation test. The results showed that nearly half of the respondents reported low self-efficacy, most had low adherence, and 60.3% experienced poor QoL. Spearman analysis demonstrated a significant correlation between self-efficacy and QoL (r = 0.647; p < 0.000), and between adherence and QoL (r = 0.684; p < 0.000). In conclusion, self-efficacy and adherence are strong predictors of quality of life in patients with type 2 diabetes mellitus at Jemursari Islamic Hospital, Surabaya. Future research should investigate interventions to enhance self-efficacy and adherence, particularly among patients with a poor quality of life, to develop more effective strategies for supporting diabetes care.